2013
DOI: 10.3109/09286586.2013.789531
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Diabetes Patients Not Receiving Annual Dilated Eye Examinations

Abstract: This study provides a snapshot of variables that may have a bearing on diabetes patients seeking annual dilated retinal examinations. Eight variables were statistically significant in affecting the timeliness of diabetic eye examinations. Thus, resolutions for these factors could be implemented for future improvement of comprehensive health care provided to those with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
1
41
2
1
Order By: Relevance
“…Most research to date assessing DFE adherence has used survey methods. 24 Self-reported data are limited not only due to response bias but also in the clinical variables that can be collected. In addition, most research has only assessed whether patients with diabetes receive an annual eye examination and does not take into account the severity of DR.…”
Section: Significance Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Most research to date assessing DFE adherence has used survey methods. 24 Self-reported data are limited not only due to response bias but also in the clinical variables that can be collected. In addition, most research has only assessed whether patients with diabetes receive an annual eye examination and does not take into account the severity of DR.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…Our results agree with a recent study from Paskin-Hall et al, who also found gender was not significantly associated with annual DFE adherence. 24 Distance from a healthcare facility or provider can be a barrier to care. Increased driving distance has been associated with poor glycemic control 38 39 and lower use of insulin.…”
Section: Non-statistically Significant Variables After Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…14 15 However, quantitative studies have their limitations. Qualitative research is complementary to quantitative research methods and is used in small groups of patients to explore complex issues in greater depth, allowing findings and themes to emerge from the data rather than testing predetermined hypotheses 16…”
Section: Introductionmentioning
confidence: 99%
“…In “Factors contributing to diabetes patients not receiving annual dilated eye examinations” by Paksin-Hall and colleagues, 6 individuals with diabetes were asked a variety of questions to get at reasons why patients with diabetes do not receive an annual dilated eye examination. 5 The study findings serve as a reminder that the social determinants of health play a critical role in the accessibility, acceptability and use of health services.…”
mentioning
confidence: 87%